Multiple myomectomy to aid fertility treatment - surgical and fertility outcomes: a retrospective cohort study - Şükür, YE (Facts Views Vis Obgyn, 2021)
OBJECTIVE: To assess the effects of multiple myomectomy at laparotomy on fertility potential of infertile women who are planning to undergo assisted reproductive technology (ART) treatment. METHODS: A retrospective single centre cohort study was conducted. Data of infertile women who were planning to undergo ART and underwent open myomectomy for multiple fibroids between January 2010 and December 2018 were reviewed. Data were collected on demographics, presenting symptoms, preoperative imaging findings, operative details, and postoperative and IVF outcomes. The primary outcome measure was the necessity for further hysteroscopic surgery prior to subsequent in vitro fertilisation (IVF) cycle. The secondary outcome measure was live birth rate. RESULTS: A total of 55 women were included in the analyses. The median number of fibroids removed was 12 (range, 3-51). Thirteen (26%) women required further surgery before embryo transfer. In women with a breached endometrial cavity, the likelihood of further hysteroscopic division of intrauterine adhesions was increased 18-fold (P=0.017). Thirty-two women underwent 45 IVF cycles, 16 of which resulted in live birth (50%). CONCLUSIONS: Infertile women with large and multiple fibroids could have good fertility outcomes following open myomectomy. Special care must be taken not to damage the uterine cavity. The intraoperative breach of the endometrial cavity seems to increase the risk of intrauterine adhesions, which may further compromise ART treatment and outcomes. Hysteroscopy prior to any embryo transfer cycle may help to optimise the endometrial cavity and fertility outcome in women who underwent multiple myomectomy.